2021
DOI: 10.4236/ojn.2021.116044
|View full text |Cite
|
Sign up to set email alerts
|

Nurses Perception of Advance Nurse Practitioners Roles in Public Hospitals: A Qualitative Study

Abstract: Aim: To explore the nurses' perceptions about the advanced nurses' practitioner's role in public hospitals in Saudi Arabia. Background: Advanced nurse practitioners are one of the leading professionals who contribute to health promotion, disease prevention, health counseling and patient education. However, misunderstandings of their roles may have an impact on the performances of the function that limits their access and the use of significant resources that can help patients to obtain treatment. Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Nevertheless, participants identifed several patientrelated, organizational, and professional positive impacts of APN in Saudi Arabia. Similar fndings were reported in recent studies in Saudi Arabia [25][26][27] and worldwide [28][29][30][31].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, participants identifed several patientrelated, organizational, and professional positive impacts of APN in Saudi Arabia. Similar fndings were reported in recent studies in Saudi Arabia [25][26][27] and worldwide [28][29][30][31].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, participants indicated that APN may face resistance from physicians, nurses, and patients, which was consistent with previous studies [34]. However, recent studies revealed that physicians [12] and nurses [26,27] in Saudi Arabia supported the implementation of APN. To the best of our knowledge, no studies have explored the patients' experiences with the care provided by APNs.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies on APN in Saudi Arabia have mainly explored the perception of healthcare professionals about these roles and its impact on organizational outcomes. For instance, previous studies have shown positive support from physicians and nurses for the integration of the NP role in the Saudi Arabian healthcare system (Almotairy et al, 2022; Banaser et al, 2021). Furthermore, Rothwell et al (2018) reported that implementing the NP role in the emergency department of a Saudi Arabian hospital was associated with decreased waiting time for patients with minor conditions and the number of patients who left the ER without being seen.…”
Section: Introductionmentioning
confidence: 99%